Institutional Management In Improving The Quality Of Early Children Education Services (PAUD) - Ismah Ismah (Universitas Nusa Cendana, 2022)
Management of early childhood education institutions (PAUD) as an effort to organize, regulate, manage and direct through an effective communication process with all components of the institution in a planned manner to achieve the goals of PAUD institutions. The pattern of early childhood education management is a design that is used by PAUD institutions to optimally manage all devices in order to improve the quality of institution. Where the management pattern is a pattern, footing, backing, pattern and reference as well as guide in managing quality PAUD institutions. Institutional management is expected to improve the quality of the institution. Can be realized through efficient ways. Does not reduce the effectiveness and optimal results carried out with appropriate leadership procedures in making every decision.